VD_FINDINFO 2016/17 vom 22. Dezember 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, PROCÈS DEVENU SANS OBJET, LITISPENDANCE, CHOSE JUGÉE | 319 let. b ch. 1 CPC (CH), 49 al. 1 CPC (CH), 50 al. 2 CPC (CH), 8a al. 7 CDPJ